Voltage‐gating of aquaporins, a putative conserved safety mechanism during ionic stresses. Issue 1 (17th October 2020) - Mom, Robin; Muries, Beatriz; Benoit, Pierrick; Robert‐Paganin, Julien; Réty, Stéphane; Venisse, Jean‐Stéphane; Padua, Agilio; Label, Philippe; Auguin, Daniel
Abstract : Aquaporins are transmembrane water channels found in almost every living organism. Numerous studies have brought a good understanding of both water transport through their pores and the regulations taking place at the molecular level, but subtleties remain to be clarified. Recently, a voltage‐related gating mechanism involving the conserved arginine of the channel's main constriction was captured for human aquaporins through molecular dynamics studies. With a similar approach, we show that this voltage‐gating could be conserved among this family and that the underlying mechanism could explain part of plant AQPs diversity when contextualized to high ionic concentrations provoked by drought. Finally, we identified residues as adaptive traits which constitute good targets for drought resistance plant breeding research. Abstract : Diversity in the response of aquaporins toward high membrane potentials. Free‐energy profile‐based correction of pf . AQP water permeability tuning through ar/R constriction arginine side‐chain conformational changes. Phenotypic diversity linked to highly variable extra‐cellular loops in plant AQPs.